Responsibility as a Component of Educational Competence - Kwieciński, Zbigniew (INSTED: Interdisciplinary Studies in Education & Society, 1998)
The author of the article analyses the problems of teachers? responsibility in the social and cultural context of contemporary education. He analyses three groups of conditions, which incline teachers to responsible behaviours. Next he considers what is the contents of teachers? responsibility. The last part of the article is concerned with the problems of education and bringing up for responsibility.